Pemberdayaan Masyarakat Kelurahan Bugangan dalam Implementasi Ketahanan Keluarga - Mien Zyahratil Umami; Romadhona Chusna Tsani; Arina Haq (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2024)
There is a lot of people who are trying to find the right place to stay and stay in the room - if there is a room in the room, there will be a small tent in the middle of the road Then the socialize well and be accepted by the surrounding environment. You can choose from any member who has the right to use the main content and harmonies, which can be used with all the harmonies. Method and data analysis. The results of the study show that the occurrence of problems in society, including juvenile delinquency, school dropouts, family disturbances and disputes, and disharmony in relationships between families in community life, are mostly caused by factors of resilience in the family.